O PT e a luta de classes no Brasil contemporâneo: o acúmulo petista de forças a favor da dominação burguesa - Gabriel, Luís Antonio Vital (2011)
The objective of this thesis is to examine the transformations occurred in the interior of the Workers Party, from its emergence in 1980, to its victorious presidential campaign in 2002. Our task, however, treads through a different way from those who understand that the changes occurred in PT represent a political maturity. In our view, this political maturity represents something else: adherence to bourgeois institutionalism. The theoretical approach of this research is anchored in the Marxist critical tradition. In a capitalist social formation as the Brazilian, the exam of a party should be aware to the complex relationships between social classes and class fractions, and more important, how these relationships are expressed in complex ways, and even covert, in the political scene. Therefore we are working with the assumption that the Workers Party itself is target of an internal and external dispute by the different political forces that acts in the Brazilian social formation. Among the empirical sources we highlight the Party s official documents, especially the resolutions of Meetings, Congresses and Governmental Programs. In short, we try to explain that the Workers Party has transformed itself in a party that contributes to the bourgeois domination in Brazil